Legal Transplants, Legal Survivals, and Legal Revivals: Towards a Reconceptualisation of The Circulation of Legal Forms in Time and Space - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
When Alan Watson introduced, back in the 1970s, the concept of a legal transplant, also known as a legal transfer, he revolutionised comparative law and comparative legal history by showing that most of legal development takes place through borrowing. However, his notion of a legal transplant conflates two quite different realities: on the one hand, the borrowing of legal forms from other, simultaneously existing legal systems (such as the transplant of the Swiss Civil Code to Atatürk’s Turkey) and, on the other hand, the rediscovery of old legal forms and their “borrowing” from long defunct legal systems (such as the rediscovery of Justinian’s Corpus Iuris Civilis by medieval lawyers in Western Europe, and the infusion of Roman ideas about contract law into existing customary rules). Although there are certain formal similarities between the two phenomena, this article will argue that they should not be conflated, especially given the sharp socio-legal difference between borrowing from a living legal system (with a functioning judiciary and legal academia) and the cultural appropriation of historical legal material for contemporary legal purposes. In this vein, the present paper – drawing on Theo Mayer-Maly’s concept of “return of juridical figures” and Tomasz Giaro’s concept of a legal “resurrection” or “borrowing from the past” – proposes to introduce a new notion of “legal revivals” and carefully delimits them from legal transplants, on the one hand, and legal survivals, on the other. One of the characteristic features of legal revivals is the use of the resources of legal history for the purposes of contemporary legal innovation.